1992
DOI: 10.1021/j100193a073
|View full text |Cite
|
Sign up to set email alerts
|

Absorption spectroscopy and dynamic and static light-scattering studies of ethidium bromide binding to calf thymus DNA: implications for outside-binding and intercalation

Abstract: By combining absorption and light-scattering spectroscopy, including photon correlation and angular distribution of absolute scattered intensity, we have studied the modes of ethidium bromide binding to calf thymus DNA at constant temperature and pH. It is found that the fraction of total bound dye molecules per nucleotide, T8D, is dependent on the counterion concentration, Cs T 8 D decreases slightly as C, is raised. Furthermore, the data indicate two modes of dye binding: intercalation and outside binding. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 18 publications
2
29
1
Order By: Relevance
“…The second mode of side binding is thought to be an association between the dye molecules and the phosphate groups at the DNA surface. The second mode is most evident at low salt and high dye concentration [18]. In this experiment, as the EB to DNA concentration ratio is low and the salt concentration is high, the second mode of binding should thus be excluded.…”
Section: Studies Of Eb-dna Intercalationmentioning
confidence: 80%
See 1 more Smart Citation
“…The second mode of side binding is thought to be an association between the dye molecules and the phosphate groups at the DNA surface. The second mode is most evident at low salt and high dye concentration [18]. In this experiment, as the EB to DNA concentration ratio is low and the salt concentration is high, the second mode of binding should thus be excluded.…”
Section: Studies Of Eb-dna Intercalationmentioning
confidence: 80%
“…At room temperature, 2 hours of stirring is needed for a complete dissolution of ctDNA. The concentrations of DNA were determined spectrophotometrically by using an extinction coef®cient of 6600 M À1 at l 260 nm, based on nucleotide phosphate [18]. To prepare the EB-DNA sample solutions, an appropriate amount of EB stock solution was added to an approximate 5.0 mL of DNA stock solution and diluted to a ®nal volume of 10.0 mL.…”
Section: Procedures For Intercalation Studiesmentioning
confidence: 99%
“…Figure 5 contains also some experimental data obtained for Calf-Thymus DNA of M w = 6.0 X 10 6 Da. Interestingly, at small ct 3 the DNA data 34 follow those of PSS, and at large ct 3 they seem to converge to curve (1) or (2). This suggests that it may be possible to describe the exlcuded volume effects appertaining to different types of polyelectrolytes by one and the same universal interpenetration function, 'P.…”
Section: Lj' =(A 2 ' M;)/(4n 3 / 2 N a 'mentioning
confidence: 86%
“…Note, similar curves are obtained for DNA, PAA, and other polyelectrolytes. 34 Two fit-parameters remain in eq 34 to 38, namely X and q. The lattice-coordination number, q, is believed to be a constant over the whole range of 0(.…”
Section: A 2c+ 3a3c 2 =0mentioning
confidence: 99%
“…6, 7) EB treatment revealed that EB could interdict cell differentiation by interfering with chromosome condensation. And virtually, EB is a cationic dye that can inhibit DNA synthesis by intercalating into the base pairs of DNA [17][18][19] and change its physical properties such as rigidity, elasticity, space structure etc., 10,11,[20][21][22] and even result in DNA molecules broken (this is approved by our other experiment about DNA damage induced by EB), then chromosomal structure damnifyed. The results indicate chromosome damage mainly locate at centromeric region (Fig.…”
Section: Resultsmentioning
confidence: 99%